Partisipasi Masyarakat Lokal dalam Pengembangan Daya Tarik Wisata Pura Lempuyang di Kabupaten Karangasem, Provinsi Bali - Desak Gede Susila; I Wayan Suardana; Ni Putu Ratna Sari (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study is motivated by the importance of local community participation in community-based tourism development, particularly at the Pura Lempuyang Tourist Attraction in Karangasem Regency, Bali. Although local communities have been involved in various tourism activities, the level of participation and distribution of roles in decision-making remain important issues to be examined. This research aims to analyze the forms of participation, levels of participation, and the impacts of local community participation in the development of tourism at Pura Lempuyang. This study employs a descriptive approach using both qualitative and quantitative data. Data were collected through in-depth interviews, observation, documentation, and questionnaires distributed to local community members. Qualitative data were analyzed thematically using NVivo, while quantitative data were analyzed using a Likert scale based on Arnstein’s ladder of participation (1969). The findings indicate that community participation is predominantly characterized as induced participation, with the main involvement occurring in operational and economic aspects of tourism. The level of participation is situated at the degrees of tokenism, particularly at the informing stage, where the community is involved through information dissemination and consultation but has limited influence on decision-making processes. Community participation also generates positive impacts on economic, social and cultural aspects, including increased income, expanded business opportunities, strengthened social interaction, and reinforcement of cultural and religious values. This study concludes that community participation in Pura Lempuyang has developed but still requires strengthening in terms of authority distribution, equitable benefit-sharing, and involvement in strategic planning to ensure more inclusive and sustainable community-based tourism development.